Between Codes and Hearts: Research and Artificial Intelligence Towards a More Human Technology (Docentes 2.0 Journal, 2025)
Technology, beyond its instrumental component, must incorporate affective and ethical dimensions that reinforce empathy along with social solidarity. The objective of this essay was to analyze how algorithmic processes can be articulated with the ethical and affective perspectives inherent to the human experience. To this end, the essay is framed within a humanist paradigm using an inductive method, with a qualitative, interpretive approach, and a narrative topic design. Throughout the text, the philosophical foundations of artificial intelligence (AI), its applications in contexts of social interaction, and its moral implications are reflected upon. Specific examples of intelligent systems oriented toward care or education are examined, contrasted with innovations of a strictly functional nature. The essay also raises the need for an interdisciplinary approach that integrates perspectives from psychology, sociology, and data science. Finally, it concludes that only through an ongoing dialogue between codes and hearts can technological development truly serve human dignity.
Keywords: Codes; humanization; research; artificial intelligence; technology